Approximation by Rational Functions in Variable Exponent Morrey–Smirnov Classes - Ahmed Kinj (Journal of Mathematics)
In this work, the direct theorem of approximation theory in variable exponent Morrey–Smirnov classes of analytic functions, defined on a doubly connected domain of the complex plane bounded by two sufficiently smooth curves, is investigated.